Reorientation Of The PPKn Paradigm For The Enhancement Of Digital Citizenship Competence In The Post-Truth Era - Roul Alvaro Prasetyo; Marzuki; Annisa Istiqomah; Muhammad Kamil Ridha (SOSIOEDUKASI, 2026)
The post-truth era, characterized by the massive spread of misinformation and the dominance of opinion, demands a reorientation of the paradigm in the teaching of Pancasila and Citizenship Education (PPKn). This research aims to formulate adaptive and innovative instructional strategies to enhance students' digital citizenship competencies in the post-truth era. This research uses a qualitative approach with a library research design that analyzes national and international academic literature published between 2016 and 2026. Data collection utilizes online literature databases, which are then qualitatively analyzed using content analysis techniques. The study results indicate that PPKn must comprehensively instill five elements of digital citizenship competence, namely: digital identity, privacy and security management, rights and responsibilities, participatory engagement, and technology skills development. To realize this, the integration of these competencies is recommended thru innovative pedagogical strategies that include project-based learning oriented toward digital action, case-based methods to dissect ethical dilemmas, and character habituation in digital citizenship within a collaborative ecosystem. In conclusion, Pancasila and Citizenship Education (PPKn) needs to promptly reorient its paradigm to enhance students' digital citizenship competencies so that they do not merely become passive consumers of information, but rather become critical, intelligent, ethical producers of digital content grounded in the Pancasila ideology amidst the challenges of the post-truth era.